Interactions of Fibrillar Insulin with Proteins: A Molecular Docking Study - Trusova, Valeriya; Zhytniakivska, Olga; Tarabara, Uliana; Vus, Kateryna; Gorbenko, Galyna (East European Journal of Physics, 2022)
During the last decades growing attention has been paid to ascertaining the factors responsible for the toxic potential of particular protein aggregates, amyloid fibrils, whose formation is associated with a range of human pathologies, including the neurodegenerative diseases, systemic amyloidosis, type II diabetes, etc. Despite significant progress in elucidating the mechanisms of cytotoxic action of amyloid fibrils, the role of fibril-protein interactions in determining the amyloid toxicity remains poorly understood. In view of this, in the present study the molecular docking techniques has been employed to investigate the interactions between the insulin amyloid fibrils (InsF) and three biologically important multifunctional proteins, viz. serum albumin, lysozyme and insulin in their native globular state. Using the ClusPro, HDOCK, PatchDock and COCOMAPS web servers, along with BIOVIA Discovery Studio software, the structural characteristics of fibril-protein complexes such as the number of interacting amino acid residues, the amount of residues at fibril and protein interfaces, the contributions of various kinds of interactions, buried area upon the complex formation, etc. It was found that i) hydrophilic-hydrophilic and hydrophilic-hydrophobic interactions play dominating role in the formation of fibril-protein complexes; ii) there is no significant differences between the investigated proteins in the number of fibrillar interacting residues; iii) the dominating hydrogen bond forming residues are represented by glutamine and asparagine in fibrillar insulin, lysine in serum albumin and arginine in lysozyme; iv) polar buried area exceeds the nonpolar one upon the protein complexation with the insulin fibrils. The molecular docking evidence for the localization of phosphonium fluorescent dye TDV at the fibril-protein interface was obtained.